2019
DOI: 10.2337/dc18-1293
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Diabetes in Patients With Primary Aldosteronism (PA) Associated With Subclinical Hypercortisolism and Prediabetes More Prevalent in Bilateral Than Unilateral PA: A Large, Multicenter Cohort Study in Japan

Abstract: To investigate the prevalence and causes of diabetes in patients with primary aldosteronism (PA) in a multi-institutional cohort study in Japan. RESEARCH DESIGN AND METHODS The prevalence of diabetes was determined in 2,210 patients with PA (diagnosed or glycated hemoglobin [HbA 1c ] ‡6.5% [ ‡48 mmol/mol]; NGSP) and compared with that of the Japanese general population according to age and sex. In 1,386 patients with PA and clear laterality (unilateral or bilateral), the effects of plasma aldosterone concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 36 publications
(41 reference statements)
3
66
3
Order By: Relevance
“…One further mechanism underlying the impairment in glucose metabolism in PA is glucocorticoid co-secretion. Although recent studies showed that higher prevalence of DM in PA patients might be associated mainly with SH [27,28], our result showed PA patients without SH, and thus with aldosterone excess alone, had a higher prevalence of DM than do sex-, age-, and BMI-matched controls. Interestingly, the DM prevalence and FPG levels were significantly decreased after ADX in PA patients without SH.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One further mechanism underlying the impairment in glucose metabolism in PA is glucocorticoid co-secretion. Although recent studies showed that higher prevalence of DM in PA patients might be associated mainly with SH [27,28], our result showed PA patients without SH, and thus with aldosterone excess alone, had a higher prevalence of DM than do sex-, age-, and BMI-matched controls. Interestingly, the DM prevalence and FPG levels were significantly decreased after ADX in PA patients without SH.…”
Section: Discussioncontrasting
confidence: 99%
“…Third, findings regarding parameters to assess glucose metabolism in PA were not fully consistent [16,[21][22][23][24][25][26]. Fourth, recent studies showed that possible cortisol co-secretion rather than only aldosterone excess itself could contribute to the impairment of glucose metabolism in patients with PA [27,28]. Finally, comparisons of the effects of adrenalectomy (ADX) and mineralocorticoid receptor antagonist (MRA) therapy on glucose metabolism in PA have only sparsely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of DM patients in the PA and SCS groups increased, which resulted to nullify a statistically significant difference in the proportion of DM patients between the 2 study groups. The fact that the risk for DM is increased in PA patients with mild glucocorticoid excess has been reported [30][31][32]; the finding was also described in Japanese patients with PA and patients with PASCS [33].…”
Section: Discussionmentioning
confidence: 71%
“…Using data from a nationwide PA registry (the Japan Primary Aldosteronism Study [JPAS] and Japan Rare/Intractable Adrenal Diseases Study [JRAS]), 7,10,11 we assessed whether changes in circulating aldosterone levels and BP were associated with changes in eGFR after surgical or MR antagonist treatment, respectively.…”
mentioning
confidence: 99%